2018
DOI: 10.1128/jmbe.v19i1.1541
|View full text |Cite
|
Sign up to set email alerts
|

Hollywood-Style Movie Trailers Increase Student Interest

Abstract: The implementation of clickers and clicker questions into classroom teaching is a well-established active-learning technique that provides more interactive classrooms and engages students with course content. Throughout the years, however, the actual clickers themselves have undergone an evolution from physical hand-held devices to web-based applications. This review explores the general advantages and disadvantages of two-main clicker styles, dedicated physical devises and web enabled clickers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Students clearly indicated that the ISLTs were interesting, increased their attention, and motivated them to learn. This was also reported by Goudsouzian (2018) which showed that the Hollywood style trailer increased students’ interest in the topic. Although students reported that the ISLTs made them pay more attention to the concepts that occurred in their learning, the ISLTs did not significantly enhance students’ emotional engagement with the follow-up full lectures, meaning that there is a gap between the emotional engagement with the ISLTs and with lectures themselves.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Students clearly indicated that the ISLTs were interesting, increased their attention, and motivated them to learn. This was also reported by Goudsouzian (2018) which showed that the Hollywood style trailer increased students’ interest in the topic. Although students reported that the ISLTs made them pay more attention to the concepts that occurred in their learning, the ISLTs did not significantly enhance students’ emotional engagement with the follow-up full lectures, meaning that there is a gap between the emotional engagement with the ISLTs and with lectures themselves.…”
Section: Discussionsupporting
confidence: 67%
“…Various pedagogical practices, such as online discussions (Clinton and Kelly, 2020; Williams and Lahman, 2011) and collaborative online learning (Curtis and Lawson, 2001; Macdonald, 2003; Zheng et al, 2015), have been implemented to engage students, aiming at improving their online learning experience and academic performance (Brown et al, 2022; Chen et al, 2010; Redmond et al, 2018). Recently, interactive digital storytelling videos (Shelton et al, 2016) and Hollywood-style movie trailers (Goudsouzian, 2018) have emerged as innovative practices for motivating students’ learning. In specific, Shelton et al (2016) created short video vignettes that incorporate imagery, data, narrative stories, and embedded interactive quiz questions into the videos to enhance student engagement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation